2014
DOI: 10.12691/ajssm-2-3-8
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Futsal Literature

Abstract: This document systematically reviews literature to provide a summary of evidence based research related to the sport of futsal. The review draws on diverse subjects including coaching, physiological, psychological, technical and tactical elements of the sport as well as reviewing subjects relating to the development of futsal. The methodology included a scoping study and review protocol to systematically review 601 documents relating to futsal; 44 of these documents were reviewed in the study. The review aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0
35

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 27 publications
(33 reference statements)
0
77
0
35
Order By: Relevance
“…Immediately afterwards, they should run back. The subjects should run the course six times with their highest speed [22].…”
Section: Participantsmentioning
confidence: 99%
“…Immediately afterwards, they should run back. The subjects should run the course six times with their highest speed [22].…”
Section: Participantsmentioning
confidence: 99%
“…; b) the necessity of updating men scenario, because the high number of players involved within futsal context in Brazil and the hard concurrence for opportunities to play in elite level within this field, what influences on the offers of practice to young players 14 ; c) the necessity to investigate RAE on women, because the negative influence of this effect on the opportunities of practice, especially because the small number of women futsal practitioners in Brazil 15 ; d) the lack of studies on sociocultural and pedagogical aspects of futsal and the necessity of descriptions about features of its participants, so as better understanding on the implications of this sport in society 16 , including Brazil…”
mentioning
confidence: 99%
“…; e) the lack of studies on futsal in English language, considering that the most of studies about this sport has been published in Portuguese or Spanish languages 16,18 ; f) the relation between RAE and pedagogical procedures involving sports and their influence on opportunities of sport participation mainly for children and young players 12 . The athletes' birthdate was obtained from the official website of both Brazilian National Futsal Leagues.…”
mentioning
confidence: 99%
“…Although researchers have examined psychological parameters such as motivation, anxiety, personality, team, leadership and injury recovery in soccer there is a significant lack of research in futsal. Specifically, futsal players have to cooperate with a common aim of achieving team targets (Travassos, Araújo, Vilar, & McGarry, 2011), the literature review showed a significant gap concerning factors that affect performance (Moore, Bullough, Goldsmith, & Edmondson, 2014). The following studies are about futsal and its psychological parameters.…”
Section: Psychological Characteristics Of Futsal Playersmentioning
confidence: 99%